Global Initiatives and Higher Education in the Fourth Industrial Revolution - Oliver, Erna (UJ Press, 2022)
The Fourth industrial Revolution (4IR) is forcing higher education (HE) into a new era where it must either actively and positively contribute to innovation, sustainability, and development or become obsolete and redundant. HE must leave its ivory tower and forge links and partnerships with society, industry, and governing bodies by delivering graduates that are holistically educated and trained to bring positive innovation and change and to address the challenges that humanity is facing in the 21st century.